RNA interference: new mechanistic and biochemical insights with application in oral cancer therapy - Buduru S (Dove Medical Press, 2018)
Smaranda Buduru,1 Alina-Andreea Zimta,2 Cristina Ciocan,2 Cornelia Braicu,3 Diana Dudea,4 Alexandra Iulia Irimie,4 Ioana Berindan-Neagoe2,3,5 1Department of Prosthetics and Dental Materials, Faculty of Dental Medicine, “Iuliu Hatieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania; 2MEDFUTURE – Research Center for Advanced Medicine, “Iuliu Hatieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania; 3Research Center for Functional Genomics and Translational Medicine, “Iuliu Hatieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania; 4Department of Prosthetic Dentistry and Dental Materials, Division Dental Propaedeutic, Aesthetic, “Iuliu Hatieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania; 5Department of Functional Genomics and Experimental Pathology, The Oncology Institute “Prof Dr Ion Chiricuta”, Cluj-Napoca, Romania Abstract: Over the last few decades, the incidence of oral cancer has gradually increased, due to the negative influence of environmental factors and also abnormalities within the genome. The main issues in oral cancer treatment consist in surpassing resistance and recurrence. However, continuous discovery of altered signaling pathways in these tumors provides valuable information for the identification of novel gene candidates targeted in personalized therapy. RNA interference (RNAi) is a natural mechanism that involves small interfering RNA (siRNA); this can be exploited in biomedical research by using natural or synthetic constructs for activation of the mechanism. Synthetic siRNA transcripts were developed as a versatile class of molecular tools that have a diverse range of programmable roles, being involved in the regulation of several biological processes, thereby providing the perspective of an alternative option to classical treatment. In this review, we summarize the latest information related to the application of siRNA in oral malignancy together with molecular aspects of the technology and also the perspective upon the delivery system. Also, the emergence of newer technologies such as clustered regularly interspaced short palindromic repeats/Cas9 or transcription activator-like effector nucleases in comparison with the RNAi approach is discussed in this paper. Keywords: RNA interference, oral cancer, therapeutic strategy, mechanistic and biochemical insights